Infrared spectra of the phases YSr₂Cu₃₋ₓMₓO7+δ, with M = Mo, W, Re and x = 0.2-0.3 - Lavat, Araceli Elisabet (2000)
Since the discovery of high-temperature cuprate superconductors much effort has been put into stabilizing new metastable phases by chemical substitution. A good example of such processes is the stabilization of YSr₂Cu₃O₇ at ambient pressure. It is well known that in spite of the fact that this material can only be prepared under high-pressure, its stabilization can be achieved at ambient conditions if other metals substitute part of the copper. In a previous paper we reported cell parameter refinement and discussed the IR spectroscopic behavior of YSr₂Cu₃₋ₓMₓO7+δ substituted phases, where M = Ti, Fe, Co, Al, Ga and Pb. In order to attain a wider insight into the spectroscopic properties of such substituted materials we have now investigated the incorporation of hexavalent Mo, W and Re in the YSr₂Cu₃O₇ lattice.